Testicular morphology of male rats exposed to Phaleria macrocarpa (Mahkota dewa) aqueous extract - Parhizkar, Saadat; Zulkifli, Suriani; Dollah , Mohammad Aziz (Mashhad University of Medical Sciences, 2014)
Objective(s):This study was designed to investigate the effect of Phaleria macrocarpa aqueous extract (PM) on spermatogenesis by observing the histological changes of testes in adult male rats. Materials and Methods: PM was prepared by boiling the dried slices of P. macrocarpa fruits followed by filtering, centrifugation and freeze-drying to obtain the powder form. Eighteen Sprague Dawley adult male rats were divided into three groups (six in each group), designated as treatment (240 mg/kg PM), negative control (distilled water) and positive control (4mg/kg testosterone) and administered via intragastric gavage for seven weeks. In the sixth week of supplementation period, each male rat was introduced to five female rats. Afterward, all rats were sacrificed and the testes were removed for histological studies. Results: PM significantly increased the number of cell and the thickness of seminiferous tubules of male rats (P<0.05). However, there was no significant effect on the volume and size of testes. The mean of spermatogonia cells numbers of PMgroups differed significantly from the negative and positive groups (P<0.05). Conclusion: PM showed potential value as an attractive alternative for improving sexual strength by increasing the number of spermatogonia cell and the thickness of the seminiferous tubules. Perhaps, PM could be suggested to be one of the herbal remedies that can improve men fertility. The results may have some clinical implication in the management of infertility.